DIGITALISATION AND AUTOMATION IN PHARMACEUTICALS FROM DRUG DISCOVERY TO DRUG ADMINISTRATION - Mannan, Abdul; Mubeen, Hajera (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
The rapid progress in the pharmaceutical industry is due to the advancement in the digitalization and automation starting from the invention to the administration of the drug. Every advancement in the development of the pharmaceutical product is associated with progress in digitalization. A drug or a drug product to be administered safely and to provide efficacy it has to undergo a long journey from its discovery, including pre-clinical and clinical trials to further product development in the research and development. The production and manufacturing systems with appropriate digitalization and automation compile the drug formulation after the servitude of the research and development (RandD) department. Later, the quality control and quality assurance systems utilize digitalization to maintain the quality and standard of the drug product. Subsequently, packaging and labeling of the drug product are carried out with effective automation. Further, the marketing and supply of the drug products are digitally monitored and dispatched to the distributors and the pharmacies. Finally, the drug product will be dispensed to the patient for its administration with a concordance of digitally monitoring for enhanced efficacy and safety. Therefore, in this review article, various strategies for digitalization and automation in the pharmaceuticals from drug discovery to drug administration are briefly discussed.